Cassava varietal improvement program at Umas Jaya Farm and its contribution to small farmer communities in Sumatra, Indonesia - Puspitorini, Palupi; Kartawijaya, Usman; Kawano, Kazuo (International Center for Tropical Agriculture, 1998)
A three-way collaboration in cassava varietal improvement and dissemination was established in 1982, in which a development-oriented private corporation (Umas Jaya Farm in Lampung, Sumatra of Great Giant Pineapple Coy of Gunung Sewu Group) provided ample facilities for varietal selection, multiplication and dissemination to a resource-limited national cassava breeding program (CRIFC), while an international organization (CIAT) contributed the basic training of research personnel and additional breeding materials. The program continued even after the CRIFC breeder left for abroad in 1989. This program is now regarded to be the best functioning cassava varietal development program in Indonesia. We selected a clone with distinctly high yield and root starch content from the original CRIFC breeding stocks, multiplied it and released it. We donated the planting stakes of this cultivar to many small farmers. cooperatives and shipped out millions of stakes to large plantations in and outside Sumatra. This new clone is now widely known as M-31 in the production fields and Adira 4 in the official registration. The economic benefit generated by the new cultivar started with the additional root harvests and additional starch produced within UJF, but it soon spread into the production fields of thousands of small farmers. Hard data, and a few extrapolations from these, indicate that Adira 4 is now planted in more than 100,000 ha and the additional economic effects caused by its adoption is more than 194 million US dollars, of which at least one half has directly entered the household income of innumerable small farmers.